Effectiveness of Moral intelligence Training on Cognitive Distortions in Patients with General Anxiety Disorder - Leili Naeimi; Fatemeh Golshani (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Anxiety is one of the most common psychiatric disorders and negatively affects cognitive function. Training ethical intelligence could be effective in reducing anxiety. The objective of this study was to determine the effectiveness of moral intelligence training on cognitive distortions in women with generalized anxiety disorder. Materials and Methods: This semi-experimental study with control group and pre-test and post-test design was conducted with participation of 60 women with generalized anxiety that were referred to the psychiatric clinic in Tehran. Participants were selected through convenience sampling and divided into two groups. Data were collected via Ellis's Cognitive Distortions Questionnaire. Data were analyzed using covariance analysis test in SPSS.22 software. Results: The mean (SD) of participants age in experimental group was 33.1 (4.7) and in control group was 33.7 (4.1). The mean (SD) cognitive distortions score in women with general anxiety in the pretest of the experimental group was 4.1 (0.50) and was decreased to 0.2 (0.28) in post-test (P<0.01, F=48.2). The mean (SD) cognitive distortions score in the control group was decreased from 3.2 (0.74) to 3.0 (0.38): P>0.05, F=0.75. Conclusion: The study showed that moral education training improved cognitive distortions of women with general anxiety. DOI: http://dx.doi.org/10.22037/ch.v6i4.23166